The Concept of Nafs in the Quran and Scholars' Thought and Its Relevance to the Character Building of Students - Lutfi Firdausi; bendaoud Nadhif (International Journal of Islamic Pedagogical Research, 2026)
The main problem is that educational practices tend to prioritize cognitive development over character and spiritual formation, resulting in a gap between the ideal concept of nafs in Islamic teachings and its implementation in addressing students’ moral challenges. This research is motivated by the importance of understanding the concept of nafs in the Qur’an and the thoughts of islamic scholars as a basis for shaping the character of students in Islamic education. The main issues addressed are how the concept of nafs is understood from the perspective of Islamic psychology, how the classification and dynamics of nafs shape personality, and how its relevance contributes to the formation of students' character. This study aims to analyze the concept of nafs, identify its classifications and developmental dynamics, and examine its implications in Islamic education. The method used is qualitative research with a literature study approach through the analysis of various relevant classical and contemporary sources. The results of the study indicate that nafs is the center of human personality, possessing spiritual, psychological, and moral dimensions, and is classified into nafs ammarah, nafs lawwamah, and nafs mutmainnah. The dynamics of the nafs are flexible and can develop through self-development processes and educational processes. In addition, the concept of nafs has strong relevance in shaping students' character through habituation, role modeling, reinforcement of spiritual values, and self-control-based evaluation. The implications of this study indicate that integrating the concept of nafs in Islamic education can produce a more holistic learning approach, thereby producing students who are not only intellectually smart but also emotionally and spiritually mature.